Interlayer exchange coupling in perpendicularly magnetized Pt/Co/Ir/Co/Pt structures. (26th October 2017) - Gabor, M S; Petrisor, T; Mos, R B; Nasui, M; Tiusan, C; Petrisor, T
Abstract: The occurrence of both interlayer exchange coupling and perpendicular magnetic anisotropy is evidenced in Pt/Co/Ir/Co/Pt magnetron sputtered structures. We point out the effect of lattice strains on stabilizing the perpendicular magnetic anisotropy. The surface magnetic anisotropy constant is around 1.76 erg cm −2 and around 1.5 erg cm −2 for the Co layers, depending on their positioning within the stack. We demonstrate a relatively high interlayer exchange constant of  −2.5 erg cm −2 at the first antiferromagnetic coupling maximum corresponding to an exchange field larger than 12 kOe. The interlayer exchange coupling shows remarkable annealing endurance being preserved for annealing temperatures up to 400 °C.